Effect of Extrusion Cooking Temperature and Mixtures of Sweetpotato (Ipomoea batatas L) and Bogor Bean (Voandzeia subterranea L THOUARS on Some Properties of Extrudates - Hidayah, Titik Nur; Mangunwidjaja, D; Sunarti, T. C.; Sutrisno, Sutrisno (Jurnal Teknologi Pertanian, 2005)
The experiment aimed to evaluate the physical properties of extrudates made up of a mixture of Bogor bean and sweetpotato was conducted in two stages. The first experiment was run to determine the best blanching time for the bean and the second one is to evaluate the effect of various levels of die temperature and mixtures of Bogor bean and sweetpotato on some physical properties of extrudates. The process for the second experiment were conducted on three levels of die temperature i.e 100°C, 140°C, and 180°C on three level of mixtures of sweetpotato/Bogor bean: 90/10, 75/25, and 60/40, respectively. The results of the first experiment indicated that a blanching treatment for 15 minutes to the bean produced a better physical quality parameter than the use of unblanched and 5 min-blanched bean as raw material. It was found that the texture (degree of crispiness), degree of expansion, viscosity and spesific gravity of the extrudates were significantly affected by the above-mentioned factors. The best physical properties were observed on the extrudate made up of a mixture of 90% sweetpotato and 10% Bogor bean at a die temperature of 100°C.   Key words: Extrusion, sweetpotato, kacang Bogor, physical properties